Genomic Tools and Genetic Improvement of Crossbred Friesian Cattle - Rahman, Md Anisur; Juyena, Nasrin Sultana; Shamsuddin, Mohammed; Bhuiyan, Mohammad Musharraf Uddin (Research in Agriculture Livestock and Fisheries, 2021)
Any genetic improvement in dairy cattle requires information on productive and reproductive performance in the given population. Animals have been selected to improve their productivity in order to increase the profitability to the farmer. As a result, selection of animals is made for higher production and a shortened productive life. The reproductive performance of Friesian cows under intensive and semi-intensive management system in Bangladesh is poor. Animal selection has historically been based on production traits, and not much attention was given to AI recording. Many attempts were taken scatterly to increase productive and reproductive potential of Bangladeshi cattle for different periods with variable achievements. Therefore, in this review article we have addressed the new tools and information that could be used to determine the level of productive and reproductive performance and to evaluate genetic factors using admixture analysis of cows bred by AI sires which affect reproductive traits of crossbred Friesian dairy cows reared in selected areas in Bangladesh. Res. Agric., Livest. Fish.8(1): 89-107, April 2021